Colour versus grey-scale display of images on high-resolution spectral OCT. Issue 5 (11th February 2009) - Brar, M; Bartsch, D-U G; Nigam, N; Mojana, F; Gomez, L; Cheng, L; Hedaya, J; Freeman, W R
Abstract : Aim: To determine whether colour or grey-scale images from high-resolution spectral optical coherence tomography (OCT) are superior in visualising clinically important details of retinal structures. Methods: Patients with macular pathologies were imaged using spectral OCT (OTI, Toronto, Canada). Two reviewers independently analysed the retinal structures and pathologies and graded them on a four-point scale on the basis of the visibility. A third reviewer masked to the results then reviewed images where there was a different score for colour versus grey scale. Results: Statistical analysis showed the grey-scale image to be significantly better in visualising the details of epiretinal membrane, photoreceptor and retinal pigment epithelium layer morphology than the colour scale image (p = 0.00088–0.0006). In 16.17% of eyes, the colour image led to the false impression of photoreceptor disruption. Conclusion: Grey-scale images are qualitatively superior to the colour-scale images on high-resolution spectral OCT. Colour images can be misleading, as the displayed colours are false colours, and the observer may see a dramatic change in colour and interpret that as a large change in the OCT reflectivity.